2022
DOI: 10.1038/s41380-022-01863-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic nurture versus genetic transmission of risk for ADHD traits in the Norwegian Mother, Father and Child Cohort Study

Abstract: Identifying mechanisms underlying the intergenerational transmission of risk for attention-deficit/hyperactivity disorder (ADHD) traits can inform interventions and provide insights into the role of parents in shaping their children’s outcomes. We investigated whether genetic transmission and genetic nurture (environmentally mediated effects) underlie associations between polygenic scores indexing parental risk and protective factors and their offspring’s ADHD traits. This birth cohort study included 19,506 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 73 publications
6
26
0
Order By: Relevance
“…Such intergenerational continuities could reflect a genetic biological inheritance 50 . Alternatively, evidence from animal and genetically-informed human studies 51 , 52 suggests a social pathway from parental genetic influences via parental characteristics, behaviour and resources that shape children’s development (genetic nurture) 51 , 53 . Consistent with this idea, we found positive associations between parent extraversion and infant approach (reflecting infant comfort in engaging with people and their environment), as well as many parental and contextual attributes that may influence infant approach (e.g., parental mental health, warmth, confidence, and supportive social context) 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Such intergenerational continuities could reflect a genetic biological inheritance 50 . Alternatively, evidence from animal and genetically-informed human studies 51 , 52 suggests a social pathway from parental genetic influences via parental characteristics, behaviour and resources that shape children’s development (genetic nurture) 51 , 53 . Consistent with this idea, we found positive associations between parent extraversion and infant approach (reflecting infant comfort in engaging with people and their environment), as well as many parental and contextual attributes that may influence infant approach (e.g., parental mental health, warmth, confidence, and supportive social context) 54 .…”
Section: Discussionmentioning
confidence: 99%
“…The association between maternal smoking and ADHD in the child appears to be strongly confounded by familial factors and may not be causal (Rice et al, 2018;Thapar et al, 2009). The same concerns may extend to drug-use (Pingault et al, 2022). However, the issue of causality does not necessarily invalidate the predictiveness of these variables.…”
Section: Pre/perinatal Predictors Of Interestmentioning
confidence: 99%
“…Parents with mental health issues may have difficulty attending to their child's needs (Dubber et al, 2015), and may be more likely to be substance users pre-and postnatally (Smedberg et al, 2015). Recent studies have suggested that the effects of environmental factors on ADHD risk may be largely captured by genetic transmission of risk from parents (Agnew-Blais et al, 2022;Pingault et al, 2022). Future studies should use intergenerational Mendelian randomization to test whether associations between pre/perinatal factors are independent from such genetic processes.…”
Section: Variance By Subgroupmentioning
confidence: 99%
“…If parental nontransmitted genes are associated with the child phenotype (i.e., ruling out genetic transmission), this effect may occur through the parental environment (Bates et al, 2018; Kong et al, 2018). Genetic nurture effects have been examined recently to investigate associations between parental genotype and offspring educational and mental health outcomes (Jami et al, 2020; Pingault, Barkhuizen, et al, 2022; Wang et al, 2021). Figure 4 is an extension of Figure 3 and additionally includes environmental parent-to-offspring effects.…”
Section: Causal Inferencementioning
confidence: 99%